MENTAL STATUS , ABILITIES MOBILIZATION AND THE RISK OF FALLS IN THE ELDERLY WITH HYPERTENSION; A CORRELATIVE STUDY - Fina Oktafiani; Dewi Hartinah; Ashri Maulida Rahmawati ((IJP) Indonesia Jurnal Perawat, 2025)
Hypertension, or high blood pressure, is a vascular disorder that hampers oxygen and nutrient supply to body tissues. Elderly individuals are prone to hypertension due to physical and psychological changes, increasing their risk of falls. Falls can significantly impact cognitive function and mobility. This study analyzes the correlation between mental status, mobility, and fall risk among elderly hypertensive individuals in Tanjungrejo Village. This cross-sectional correlation study involved 64 randomly selected participants from Tanjungrejo Village in November 2024. Mini Mental State Exam (MMSE), Elderly Mobility Scale (EMS), and Berg Balance Scale (BBS) assessed mental status, mobility, and fall risk, respectively. Spearman Rank test analyzed the data.Results showed: most elderly hypertensive individuals (45.3%) had probable cognitive impairment. Majority (57.8%) demonstrated independent mobility. Most participants (57.8%) had moderate fall riskA significant correlation exists between mental status, mobility, and fall risk among elderly hypertensive individuals in Tanjungrejo Village, Jekulo Subdistrict, Kudus Regency (p-value  0.05).